2012
DOI: 10.1016/j.febslet.2012.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure analysis of the translation factor RF3 (release factor 3)

Abstract: a b s t r a c tThe bacterial translational GTPases release factor RF3 promotes translation termination by recycling RF1 or RF2. Here, we present the crystal structures of RF3 complexed with GDP and guanosine 3 0 ,5 0 -(bis)diphosphate (ppGpp) at resolutions of 1.8 and 3.0 Å, respectively. ppGpp is involved in the socalled ''stringent response'' of bacteria. ppGpp binds at the same site as GDP, suggesting that GDP and ppGpp are two alternative physiologically relevant ligands of RF3. We also found that ppGpp de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…In addition, examining the surface potential in RF3 from D . vulgaris (Figure 6G) (Kihira et al, 2012) we find a similar positive surface potential in the same position as we observed for RF3 from E . coli .…”
Section: Resultssupporting
confidence: 87%
“…In addition, examining the surface potential in RF3 from D . vulgaris (Figure 6G) (Kihira et al, 2012) we find a similar positive surface potential in the same position as we observed for RF3 from E . coli .…”
Section: Resultssupporting
confidence: 87%
“…High-resolution crystal structures provide insights into these interactions. So far, several (p)ppGpp-bound structures have been solved, including E. coli RNA polymerase (PDB: 4JK1 and 4JKR, ~4 Å resolution) (Mechold et al, 2013; Zuo et al, 2013), lysine decarboxylase (PDB: 3N75, 2.0 Å) (Kanjee et al, 2011), adenylosuccinate synthetase (PDB: 1CH8, 2.5 Å) (Hou et al, 1999), Desulfovibrio vulgaris translation release factor 3 (PDB: 3VR1, 3.0 Å) (Kihira et al, 2012), S. aureus primase (PDB: 4EDT, 2.01Å) (Rymer et al, 2012), Aquifex aeolicus PPX/GPPA phosphatase (PDB: 2J4R, 2.71 Å) (Kristensen et al, 2008), and B. subtilis Obg (PDB: 1LNZ, 2.6 Å) (Buglino et al, 2002). Here, we described the 1.67 Å resolution crystal structure of pppGpp-bound S. aureus GMK, which is the highest resolution achieved for a (p)ppGpp-bound structure to date.…”
Section: Discussionmentioning
confidence: 99%
“…ppGpp can also bind to and affect the activities of a large number of other proteins in addition to RNAP (1,2), thereby playing roles in processes as diverse as DNA replication (8,9), translation (10)(11)(12), nucleotide metabolism (2,(11)(12)(13)(14), ribosome biogenesis (11,12,15,16), amino acid decarboxylation (17), polyphosphate metabolism (18), and ppGpp metabolism itself (11,19,20). Our studies were designed to distinguish the effects of ppGpp on gene expression resulting from its binding to RNAP versus other cellular targets.…”
mentioning
confidence: 99%